”Laknat Ziyarah Qubur Bagi Perempuan” (Studi Takhrij Hadis) - Maryono, Muhammad; Riza Hadikusuma, Riza (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2022)
This article was written with the intention of knowing the quality of the hadith that curses women who make pilgrimages to the grave. The focus of his writing leads to the research of the hadith sanad which has several lines of narration, namely from the companions of Abu Hurairah, Ibn Abbas, and Hassan bin Sabit. The conclusion is that in terms of the sanad of the hadith, the quality is authentic. Meanwhile, from the point of view, it can be concluded that the prohibition should not make pilgrimages because the hadith of the prophet means for women who often carry out pilgrimages to the grave because the hadith uses sighot or the form of mubalaghoh (zawwarot).